Drug Transport across Porcine Intestine Using an Ussing Chamber System: Regional Differences and the Effect of P-Glycoprotein and CYP3A4 Activity on Drug Absorption - Yvonne E. Arnold; Julien Thorens; Stéphane Bernard; Yogeshvar N. Kalia (MDPI AG, 2019)
Drug absorption across viable porcine intestines was investigated using an Ussing chamber system. The apparent permeability coefficients, Papp,pig, were compared to the permeability coefficients determined in humans in vivo, Peff,human. Eleven drugs from the different Biopharmaceutical Classification System (BCS) categories absorbed by passive diffusion with published Peff,human values were used to test the system. The initial experiments measured Papp,pig for each drug after application in a Krebs–Bicarbonate Ringer (KBR) buffer and in biorelevant media FaSSIF V2 and FeSSIF V2, mimicking fasted and fed states. Strong sigmoidal correlations were observed between Peff,human and Papp,pig. Differences in the segmental Papp,pig of antipyrine, cimetidine and metoprolol confirmed the discrimination between drug uptake in the duodenum, jejunum and ileum (and colon); the results were in good agreement with human data in vivo. The presence of the P-gp inhibitor verapamil significantly increased Papp,pig across the ileum of the P-gp substrates cimetidine and ranitidine (p < 0.05). Clotrimazole, a potent CYP3A4 inhibitor, significantly increased Papp,pig of the CYP3A4 substrates midazolam, verapamil and tamoxifen and significantly decreased the formation of their main metabolites. In conclusion, the results showed that this is a robust technique to predict passive drug permeability under fasted and fed states, to identify regional differences in drug permeability and to demonstrate the activity of P-gp and CYP3A4.